Spontaneous Quick Resolution of Uncombable Hair Syndrome-Like Disease - Ramot, Yuval (Skin Appendage Disord, 2019)
Uncombable hair syndrome (UHS) is a unique hair shaft disease characterized by frizzy, straw-colored hair, which is resistant to combing and brushing. Familial cases have been described, and recently mutations in genes related to trichohyalin production have been reported as the cause for this condition. UHS usually manifests during early childhood, and gradually resolves at puberty. Herein, we report on a 2-year-old boy whose hair changed to a UHS-like phenotype “overnight” with no apparent trigger. The condition resolved abruptly after 9 months. Genetic analysis revealed a heterozygous variant in the PLCD1 gene, which has been connected to hair development. This case raises the possibility that a genetic cause can lead to a temporary change in hair shaft appearance, possibly after exposure to a yet unknown external trigger.